Teacher Certification: The Efforts to Increase Teachers’ Involvement in Islamic Basic Education - Amiruddin Siahaan; Amiruddin Amiruddin; Titik Ningsih; Wahyu Sakban; Tuti Ernawati (Universitas Pahlawan Tuanku Tambusai, 2023)
Economic well-being is a latent problem for teachers in education, so the government is trying to program teacher certification. This study aims to analyze teacher certification as an effort to increase teacher involvement in educating students at the basic Islamic education level. As for this type of research, it includes a qualitative approach with library research methods. Sources of data and study analysis materials use scientific literature, including books, articles, seminar proceedings, and final assignments (thesis, thesis, dissertation). The data is obtained from credible sources such as Google Scholar and Sinta. The results of this study conclude that the implementation of teacher certification is expected to increase the ability of teachers which in turn has an impact on improving the quality of education in this country much better. The hope is that after certification, teachers should be able to fulfill the four elements as stated in the teacher and lecturer law article 10 and government regulations regarding national education standards article 28 namely pedagogic, character, professional and social competence.